INCIDENCE OF INFECTION DURING SALVAGE CHEMOTHERAPY REGIMENS IN PATIENTS WITH RELAPSED/ REFRACTORY LYMPHOMAS: AN EXPERIENCE OF A TERTIARY CARE CENTER - Devi , Kanta; Shaikh, Muhammad Usman; Ali, Natasha; Khan, Maria; Adil, Salman Naseem (Infectious Diseases Journal of Pakistan, 2022)
Background: Mortality from lymphomas has improved over the years with newer chemotherapy regimens. However, life-threatening infections caused by immunosuppression due to chemotherapy remain a major cause of morbidity and mortality. Due to patients being lost-to-follow-up in developing countries, it is difficult to accurately quantify the incidence of infection. Thus, this prospective study aims to assess the rate of infection in lymphoma patients on salvage chemotherapy. Material and Methods: A prospective study was conducted at a tertiary care hospital in Karachi, Pakistan. Patients aged 16-65 years of both gender and appropriate organ function were included. Patients with pre-existing cardiovascular disease and active infections were excluded. STATA version 16 was used to analyze the data. Results: A total of 98 patients were included. The mean age of participants was 43.7 ± 15.5 years. Males were 73.7% of all patients and females were 26.3%. Febrile neutropenia was found in 4.1% of patients, all of whom had DLBCL (refractory in 2 patients and relapsed in 2 patients). The mean age of patients was 41.7 ± 13.5 years. Sepsis was found in 14.1% of patients, of which 8 had NHL and 6 had HL. Half of all patients with sepsis had late relapse. The mean age of all patients with sepsis was 47.4 ± 18.2 years, which was not statistically significant from the remainder of the sample. Conclusion: Infectious complications are high in lymphoma patients on salvage chemotherapy. Often, they may progress to sepsis, with its associated high morbidity and mortality in this vulnerable patient population. Keywords: Infection, Sepsis, Salvage chemotherapy, Lymphoma